Differentiable Planning for Optimal Liquidation - Pennacchio, Alan A.; Barros, Leliane N. de; Mauá, Denis D. (Anais do Brazilian Workshop on Artificial Intelligence in Finance (BWAIF); 2022: Anais do I Brazilian Workshop on Artificial Intelligence in FinanceDO - 10.5753/bwaif.2022.223144, 2022)
Optimal liquidation consists of selling large blocks of single stocks within given time frames optimally with respect to specified risk-sensitive objectives. In this paper, we extend the Almgren-Chriss model for the liquidation process to a more generic and realistic setting and present a differentiable planning algorithm to solve it. We evaluate the performance of the proposed method through experiments, demonstrating the potential of differentiable planning for optimal liquidation in realistic scenarios.